Study the Effect of Partial of Replacement of Industry Cement ‎Waste with Sand on Mechanical and a Partial Property of Concrete ‎and Mortar ‎ (Journal of University of Babylon for Engineering Sciences, 2018)
The technical and economic problems that arise from transportation industry cement waste outside the cement plant ,as well as the sever pollution of the surrounding environment by this waste ,make the subject matter worth studies .This study was thus conducted to examine the feasibility of using industry cement waste in concrete and mortar mixes as partial replacement for sand. The percentage of industry cement waste replacement used from 5% and 30% in mortar and concrete respectively .The presence of industry cement waste as sand partial replacement increases the compressive strength of relatively lean mixes, especially at early age ,while adversely effects the strength of rich mixes .The inclusion of 25% of industry cement waste by weight of sand in lean mixes, improvement in compressive strength by about 30% and 20% in concrete and mortar for 7 days respectively. The effect of replacing industry cement waste (ICW ) as a sand partial on the compressive strength of concrete and mortar mixes of resistance Portland cement higher than ordinary Portland cement where discussed by several authors. Other concrete properties including modulus of rupture and density show trend similar to that observed in compressive strength.